2018
DOI: 10.1051/matecconf/201816304006
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobisation of mortars containing waste polyurethane foam

Abstract: This paper investigates the physical and mechanical properties of mortars modified with waste polyurethane foam (WPF) and the influence of hydrophobising agents on the physical characteristics. The sand was substituted with WPF (2-4 mm grain size) in the mortars which consisted of 5, 10 and 15% of foam, respectively. The contact angle of lightweight mortars was determined (θw) in the function of time, prior to and after the frost resistance test. The surface free energy characterizing the wettability and adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Similar conclusions were reported by different authors, especially for cases in which particles of polysiloxane resign were too large to penetrate the tiny porous structure of concrete [ 32 , 35 ]. Łukowski [ 36 ] and other researchers [ 28 , 34 , 35 ] confirmed that the geometry and composition of the polymer particle, not the chemical nature of polymer compound, had significant relevance during the formation of the polymer coating. As a result of water penetration thorough the pervious coating and frost activity, stratification at the joint of the concrete base and the polymer coating is possible.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar conclusions were reported by different authors, especially for cases in which particles of polysiloxane resign were too large to penetrate the tiny porous structure of concrete [ 32 , 35 ]. Łukowski [ 36 ] and other researchers [ 28 , 34 , 35 ] confirmed that the geometry and composition of the polymer particle, not the chemical nature of polymer compound, had significant relevance during the formation of the polymer coating. As a result of water penetration thorough the pervious coating and frost activity, stratification at the joint of the concrete base and the polymer coating is possible.…”
Section: Introductionmentioning
confidence: 88%
“…It was showed that the hydrophobization of LC composites containing recycled polyurethane foam increased frost resistance by over 80%, compared to the reference samples [ 34 ]. However, surface hydrophobization is not always efficient in the improvement of concrete characteristics, especially when the concrete contains industrial waste [ 24 , 30 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The contact angle was 157.3 • and the water absorption was reduced by about 92.51%. Hydrophobisation of lightweight mortars containing waste polyurethane foam carried out in work [36] increased frost resistance up to 84% compared to the model samples. The work of Barnat-Hunek et al [37] is another example confirming the effectiveness of hydrophobisation which has helped to protect the mortar with expanded cork from the destructive effects of frost.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, in recent years the use of various hydrophobic agents, to minimize the decomposition rate of porous materials, has been widely discussed [36][37][38]. Furthermore, the concentration and type of the active substance in the agent constitute a very crucial factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation